Acute phlegmonous appendicitis - Chesca, A.; Sandle, T.; Abdulina, G.A.; Anamaria, P. (KU Publ., 2022)
Acute phlegmonous appendicitis is an outstanding topic in medicine. The issue can be approached in terms of diagnosis and the importance of practical surgery. The clinical diagnosis can be supported by macroscopic and microscopic anatomo-pathological diagnoses. The microscopic diagnosis can be established after studying morphological characteristics observed by analogy with microscopic preparations stained by traditional and special methods. Pathological microscopic preparations can be analyzed and compared with histological preparations that display normal appendix. This paper presents some best practice examples. To provide a precise explanation to medical staff, a series of images of microscopic slides were taken from patients for microscopic analysis. The creation of permanent microscopic slides was based on knowledge of the steps required for classical histological methods using standard H&E staining techniques. Samples were taken from patients of both sexes, children under 16 years old, from urban and rural areas. It is important to clarify misunderstood epidemiological features of appendicitis. Perforating and non-perforating appendicitis, apparently, are separate in nature, and since the need for spontaneous resolution of appendicitis is essential. It is important to have better quality reference materials to enable the medical staff to make the correct decision; this paper seeks to add to this area of knowledge. Ensuring that the diagnosis is correct can have important implications for the management of appendicitis suspicion. This must be supplemented with histological assessments together with important personal, heredocolateral antecedents in the patient’s pathological history. For example, determinations of the lymphocytopenia and neutrophil-lymphocyte ratio can predict bacteremia better than conventional infection markers in the emergency department. Histopathological analysis remains important for such determinations.
Жедел флегмонозды аппендицит
Острый флегмонозный аппендицит
Keywords: appendix; children; microscopic analyze; diagnostic; appendicitis; histopathological examinations